Alignment of Community Pharmacy Foundation Grant Funding and the Evolution of Pharmacy Practice in the United States of America - Brittany Hoffmann-Eubanks; Anne Marie Kondic; Brian J. Isetts (MDPI AG, 2019)
The Community Pharmacy Foundation is a non-profit organization dedicated to the advancement of community pharmacy practice and patient care delivery through grant funding and resource sharing. Since 2002, CPF has awarded 191 grants and over $9,200,000 (US dollars) in research and project grants. The purpose of this manuscript is to highlight the evolution of pharmacy practice and pharmacy education in the United States through the presentation of exemplary cases of Community Pharmacy Foundation funding that is aligned with new care delivery models and approaches to the advancement of patient-centered pharmacy care. Pharmacy began in colonial America as the United States of America was just beginning to form with apothecary shops and druggists. Over time, the pharmacy industry would be revolutionized as America became urbanized, and drug products became commercially produced. The role of the pharmacist and their education evolved as direct patient care became a clear expectation of the general public. By the 1990s, the pharmacy profession had carved out a new path that focused on pharmacist-led, patient-centered pharmaceutical care and medication therapy management services. The Community Pharmacy Foundation grant funding has aligned with this evolution since its founding in 2000, and multiple exemplary grants are presented as support. As the role of pharmacists again transitions from a fee-for-service model to a value-based model, the Community Pharmacy Foundation continues to provide grant funding for research and projects that support the advancement of community pharmacy practice, education, and expanded training of pharmacists.